Season physical performance of professional soccer players. Match-play evaluation of a Greek Super League team - Mitrotasios, M.; Ispyrlidis, I.; Mantzouranis, N.; Vassiliades, E.; Armatas, V. (Journal of Physical Education and Sport, 2021)
The aim of this study was to analyze the physical performance of the players in one of the top-3 teams of the national Superleague comparing the full-season matches in relation to the tactical position of the players and the match location. Eighteen (n=18) professional players aged 27±3.3 yr, with body mass 77.1±6.9kg and stature 180.5±55 cm were assessed. The StatSport GPS Tracker (FIFA Approved) recorded in real-time the elite individuals' physical performance in 30 official matches (15 home & 15 away) during the 2018-2019 season. 201 match-play observations were evaluated according to the players' positional role in their team. The covered distances (m) of the starting line-up players (goalkeepers excluded) during the in-season matches were evaluated in 6 intensity zones (Z1=<1.5m.sec-1, Z2=1.5-3m.sec-1, Z3=3-4m.sec-1, Z4=4-5.5m.sec-1,Z5=5.5-7m. sec-1, Z6=>7m.sec-1). For the comparison of the studied variables, the MANOVA was applied along with the Bonferroni test.The descriptive analysis showed that the match-playperformance of the players was as high as 10289±729m. In addition, significant differences were observed in theplayers' covered distancesin all intensity zones in relation to their positional role (p<0.001). Specifically, during the matches, central midfielders (10961±698m), full-backs (10649±668m) and wide midfielders/wingers (10216±498m) covered a greater amount of distances in all playing zones (p<0.001), compared to central defenders (9939±559m) and forward players (9728±587m).In contrary, no significant interactionwas recorded between the players'physical performance in all intensity zones and the match location. Moreover, in the maximal intensity zones from 4 to >7m.sec-1, the covered distances by the players were significantly lower (p<0.05) for central defenders (1614m) in relation to full-backs (2404m), central midfielders (2354m), forwards (2092m) and wide midfielders/wingers (2085m). Finally, no significant differences were presented between both the players' positional role and their covered distances in all intensity zones and the match location. Summarizing, the physical performance of the players during the in-season matches confirms that the studied Greek club meets the high physical conditioning standards of the elite soccer clubs that participated in other European national leagues.